Idylls of the wanderer : outside in literature and theory - Sussman, Henry (UPCC book collections on Project MUSE., 2007)
An extended inquiry into the dimension of exteriority constructed by philosophical systems and literary works, this text reviews works by James Baldwin, Walter Benjamin, William Faulkner and James Joyce.